Sams teach yourself java 2 online in web time - Gilbert, Stephen; McCarty, Bill. ([S.l.] : Sams Publishing, 1999)
Sams Teach Yourself Java 2 Online in Web Time helps the first-time programmer or the programmer new to Java to learn Java and its APIs. Written in a warm and familiar style, Teach Yourself Java in WebTime requires no previous programming experience. It incorporates the proven instructional techniques of the Teach Yourself series, including end-of-section quizzes and programming exercises that allow you to review and expand upon the concepts and skills presented in that chapter. The learning experience is further enhanced with an instructional Web site.